A 3D Lithium/Carbon Fiber Anode with Sustained Electrolyte Contact for Solid‐State Batteries. Issue 3 (4th December 2019) - Zhang, Ying; Shi, Yang; Hu, Xin‐Cheng; Wang, Wen‐Peng; Wen, Rui; Xin, Sen; Guo, Yu‐Guo
Abstract: To reconcile the energy storage ability and operational safety of lithium metal batteries (LMBs), a transformation from a liquid to a solid‐state system is required. However, Li volume variation, poor interfacial contact, and high operation temperatures hinder its practical applications. To address the above issues, here, an integral structure design for solid‐state LMBs is shown, in which a Li‐preinfused 3D carbon fiber (Li/CF) anode is ionically connected to a cathode via an autopolymerized gel electrolyte. The gel electrolyte helps to encapsulate the liquid electrolyte within the Li/CF anode and the cathode to improve the interfacial contact. The gel also serves as a reservoir that balances the liquid electrolyte supply during repeated Li stripping/plating process. As a result, the symmetrical cells and full cells with Li/CF electrodes exhibit improved cycling stability and effective suppression of dendrites at ambient temperature. This work facilitates the realization of solid‐state LMBs with high energy and high safety. Abstract : A structural integration design is reported to combine a 3D Li/carbon fiber (CF) anode and cathode materials via an in situ polymerized gel for safer Li metal batteries. The gel solves the ionic contact issue by encapsulating preloaded liquid electrolytes within Li/CF structure, and balances the liquid electrolyte supply in the presence of Li volume change.